PENERAPAN MODEL PEMBELAJARAN DISCOVERY UNTUK PEROLEHAN BELAJAR PEMBAGIAN BILANGAN BULAT DI SMP - Abdulrani, Abdulrani; Asrori, H.M.; Suib, Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research was to find: 1) The basic pattern of learning mathematics in learning discovery model for acquisition of learning division of integers class SMP. 2) Implementation of Mathematics learning with discovery learning model developed for acquisition of learning division of integers in class VII of SMP Negeri 1 Sandai. 3) The acquisition of learning division of integers by using discovery learning model in class VII  SMPi. This research used a qualitative approach with research method and used or utilization of existing learning models. Data source in this research was teachers of Mathematics and students of class SMP. The results of the research was : (1) The basic design of relevant learning on integer material was designed by using scientific approach; observing, asking, reasoning, trying and communicating. (2) Implementation of Mathematics learning with discovery learning model, with steps: division of study group, learning implementation, group discussion, quiz awarding and group awards. (3) The acquisition of learning of the division of integers found that the behavior of students in carrying out the discussion activities as a whole showed a good attitude with high tolerance and created of good cooperation and responsibility even the existence of a confidence in expressed his opinion.  On the competence of mastery of learning materials on the cognitive aspect obtained the value of all groups of students has reached 100% complete learning with the lowest score 66 and the highest 82. Keywords: Implementation of Discovery Learning Model, Acquisition of Learning, Division of Integers